HUBUNGAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG KESEHATAN REPRODUKSI DENGAN SIKAP SEKSUAL PRANIKAH - Widiatrilupi, Raden Maria Veronika; Henny Lantu, Nouva (NHM PRESS, 2024)
Background: Knowledge about reproductive health plays a crucial role in shaping sexual attitudes of adolescent girls, especially in the context of premarital sexual attitudes. The quality of information received by adolescents about reproductive health can influence their decisions and attitudes regarding sexual activity. In the Kendahe Health Center working area, there are concerns about the low level of knowledge of adolescent girls about reproductive health and its impact on premarital sexual attitudes. Objective: This study aims to analyze the relationship between the level of knowledge of adolescent girls about reproductive health and premarital sexual attitudes in the Kendahe Health Center working area. Method: This study used a cross-sectional research design involving 39 adolescent girls as respondents. Data were collected through a questionnaire that measured the level of knowledge about reproductive health and premarital sexual attitudes. Statistical tests were conducted to determine the relationship between the two variables using the p-value. Results: Based on data analysis, it was found that there was a significant relationship between the level of knowledge about reproductive health and premarital sexual attitudes in adolescent girls in the Kendahe Health Center working area. The results of the statistical test showed a p-value of 0.000, which is smaller than 0.05, indicating a significant relationship. Conclusion: This study revealed that the level of knowledge about reproductive health is significantly related to premarital sexual attitudes of adolescent girls. Adolescent girls with better knowledge about reproductive health tend to have more positive and responsible premarital sexual attitudes.